Legal Construction for The Establishment of Land Banks in Land Procurement for Fair Public Interest - Ida Ayu Putu Sri Astiti Padmawati; I Made Suwitra; Putu Ayu Sriasih Wesna (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
The purpose of this study is to examine and describe the urgency of establishing a land bank and the implications of the authority of a land bank in realizing land acquisition for the public interest that is equitable in Indonesia. The method used in this research is normative legal research and the approaches used are the legislative approach, the historical approach, the comparative approach and the conceptual approach. The results of this research indicated that land is driven by Indonesia's urgency to the problem of very large land needs, which will later be used as a forum for investment activities. The implication of the Land Bank's Authority in the Job Creation Act and the government regulation of land banks raises several problems, namely, firstly, overlapping authorities with other land institutions. Second, the strengthening of Land Management Rights related to the authority of the land bank is intended to provide facilities and/or licensing services more aimed at increasing investment than as much as possible for the prosperity of the people, this has a very broad impact including 1) Causing an increase in the number of Agrarian Conflicts; 2) Bringing back the principle of Domein Verklaring; 3) Weakening of the existence of customary law communities and their ulayat lands; and 4) the overlapping authority of the land agency